Biomarkers of inflammation in patients with myocardial infarction and heart failure with preserved and mid-range ejection fraction: 5-year prospective follow-up - N. A. Musikhina; T. I. Petelina; A. I. Kostousova; L. I. Gapon; E. A. Gorbatenko; I. S. Bessonov (Российский кардиологический журнал)
Aim. To evaluate the effect of biomarkers of inflammation on the long-term prognosis in patients with myocardial infarction (MI) and heart failure (HF) with preserved and mid-range ejection fraction according to a registry of percutaneous coronary interventions (PCI).Material and methods. A total of 135 patients with MI included in the PCI registry in 2012-2013 were examined. Group 1 included 89 patients with HF with mid-range ejection fraction (HFmrEF) — 40-49%; group 2 included 46 patients with HF with preserved ejection fraction (HFpEF) — ≥50%. Biomarkers of inflammation were determined at admission to the hospital, after 12 and 60 months.Results. Eighteen people died during the follow-up period. The survival rate of patients in the compared groups after 60 months did not differ (group 1 — 85,0%; group 2 — 89,1%, p=0,492). Mortality predictors were the platelet count (HR, 1,011; 95% CI, 1,003-1,019; p=0,010), homocysteine level (HR 1,172; 95% CI, 1,008-1,364; p=0,040), MMP-9 >249 ng/ml (HR, 7,052; 95% CI, 1,346-36,950; p=0,021). In both groups there was a decrease in survival in patients with high levels of MMP-9 (>249 ng/ml). In group 1, mortality was higher among patients with platelet count >245*109/l. In both groups the levels of inflammatory markers exceeded the standard values for the entire period of follow-up. The dynamics of NT-proBNP, hs-CRP, TNF-α and homocysteine had a unidirectional pattern, in particular, a decrease in parameters after 12 months, followed by their increase after 60 months.Conclusion. Levels of MMP-9, homocysteine, and platelets were the factors that influenced 5-year survival in the general group of patients after MI and PCI. In the group with HFmrEF, MMP-9 and platelets had a negative impact on the prognosis. In patients with HFpEF, reduced survival was associated only with high levels of MMP-9. The dynamics of markers of systemic inflammatory response and NT-proBNP indicates the prolonged inflammatory process in both groups of patients, persisting for 5 years after MI.